Early child care and child development: For whom it works and why - Christina Felfe; Rafael Lalive (Center for Economic Studies and ifo Institute (CESifo), 2012)
Many countries are currently expanding access to child care for young children. But are all children equally likely to benefit from such expansions? We address this question by adopting a marginal treatment effects framework. We study the West German setting where high quality center-based care is severely rationed and use within state differences in child care supply as exogenous variation in child care attendance. Data from the German Socio-Economic Panel provides comprehensive information on child development measures along with detailed information on child care, mother-child interactions, and maternal labor supply. Results indicate strong differences in the effects of child care with respect to observed characteristics (children's age, birth weight and socio-economic background), but less so with respect to unobserved determinants of selection into child care. Underlying mechanisms are a substitution of maternal care with center-based care, an increase in average quality of maternal care, and an increase in maternal earnings.
Keywords: J13; I21; I38; 330; child care; child development; marginal treatment effects; Kinderbetreuung; Wirkungsanalyse; Kinder; Schätzung; Deutschland